Determination of local wind energy potentials using climate modeling - Çöllü, Kamil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2016)
After the industrial revolution, the needs of coal and other fossil fuels has been increasing day by day. Intensive burning of fossil fuels has resulted in a rise in the atmospheric CO2 concentration. In the 18th century, the amount of CO2 in the atmosphere was almost 280 ppm and now this value is more than 400 ppm. As a result of that, climate is changing rapidly and predicting the climate and its variables, such as wind speed and direction, is more di cult than before. It is more important to use renewable energy to reduce CO2 emission to the atmosphere. To be able to do, wind energy is a good option and it is a rising star in the renewable energy market. Determining location of wind power plant according to wind direction and wind speed of region is vital for market. In order to solve these kinds of problems, an alternative method is applied in this study. To predict wind direction and speed according to the climate change, rstly, I used RegCM4, one of Regional Climate Model version of The Abdus Salam International Centre for Theoretical Physics (ICTP), which is developed in ICTP, for simulating the climate variables and, then I used an open source software Winds on Critical Streamline Surfaces (WOCSS), which is developed by Dr. Francis L. Ludwig, for projecting the wind direction and speed. The result of this study shows wind speed will increase at the Canakkale Biga region at the future.
Keywords: Climatology -- Mathematical models.; Wind energy conversion systems.